Positive Fluid Balance Is Associated with Higher Mortality and Prolonged Mechanical Ventilation in Pediatric Patients with Acute Lung Injury - Heidi R. Flori; Gwynne Church; Kathleen D. Liu; Ginny Gildengorin; Michael A. Matthay (Critical Care Research and Practice)
Introduction. We analyzed a database of 320 pediatric patients with acute lung injury (ALI), to test the hypothesis that positive fluid balance is associated with worse clinical outcomes in children with ALI. Methods. This is a post-hoc analysis of previously collected data. Cumulative fluid balance was analyzed in ml per kilogram per day for the first 72 hours after ALI while in the PICU. The primary outcome was mortality; the secondary outcome was ventilator-free days. Results. Positive fluid balance (in increments of 10 mL/kg/24 h) was associated with a significant increase in both mortality and prolonged duration of mechanical ventilation, independent of the presence of multiple organ system failure and the extent of oxygenation defect. These relationships remained unchanged when the subgroup of patients with septic shock (n=39) were excluded. Conclusions. Persistently positive fluid balance may be deleterious to pediatric patients with ALI. A confirmatory, prospective randomized controlled trial of fluid management in pediatric patients with ALI is warranted.